Pengaruh Cyberloafing dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Bosowa Propertindo Kota Makassar - Farda Toatubun; Samsul Rizal; Nurinaya Nurinaya (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of cyberloafing and work discipline on employee performance at PT Bosowa Propertindo Makassar. The research is driven by the rapid adoption of digital technology in workplaces, which potentially triggers internet usage for personal interests during working hours. This study employs a quantitative approach, with data gathered through questionnaires distributed to 30 employees using a total sampling technique. Data analysis was conducted using multiple linear regression, supported by validity, reliability, and classical assumption tests processed through SPSS software. The results reveal that cyberloafing has a significance value of 0.174 (> 0.05), indicating it does not have a significant impact on employee performance despite exhibiting a negative relationship. In contrast, work discipline shows a significance value of 0.000 (< 0.05), demonstrating a positive and significant effect on performance. Simultaneously, both variables account for 37.2% of the variance in employee performance, while the remaining 62.8% is influenced by external factors. These findings suggest that improving work discipline is the primary factor for enhancing organizational productivity. Consequently, the company is encouraged to strengthen disciplinary regulations and monitor internet usage to maintain optimal performance in the modern digital era.